(3ebGdI aj GdehdhO dSHYI CTgQs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd Cfg bO jXf Cf bhd GHbQGW ai GdCWaGd GdehdhOjf dSHYI GTgQ bO jNGda HYVg HYVkG ddUhQI NeSI hKdGKhf jhekG s
(3BNQgG (B:s
(3jYfi Efg EROGJ Ydi GdfUa jhe ef jhe cGf eG jbY ef GdTgjQ GdSGHY CcKQ ef YTQjf jhekG JeJ ebGdI LGdjfhS s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdMGOjI YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs